A taxonomic study of the Oriental leafhopper genus Raabeina Dworakowska (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini), with descriptions of five new species and one new record from China - Zhang, Yalin; Cao, Yanghui (Zootaxa, 2011)
Eight species of the genus Raabeina are illustrated, including three previously described species and five new species are described: Raabeina acutata, R. biangulara, R. bubengensis, R. curtihamata and R. gracila spp. nov. One species, R. fuscofasciata Dworakowska n. rec, is newly recorded from China. A key to males of Raabeina is provided.